2013
DOI: 10.3109/00365548.2013.851414
|View full text |Cite
|
Sign up to set email alerts
|

Liver abscess due to Klebsiella pneumoniae: Risk factors for metastatic infection

Abstract: Clinicians must be aware of potential metastatic infections in patients with KPLA, especially if they have diabetes mellitus and thrombocytopenia. The APACHE II score was predictive of mortality in patients with KPLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 19 publications
5
46
2
2
Order By: Relevance
“…We observed that the crude annual incidence of PLA and KP-PLA increased significantly from 1994–2004 to 2004–2015, which could be due to larger number of inpatients and improved early diagnostic techniques. In short, PLA and KP-PLA are common health problems in mainland China, which consistent with the recent epidemiological trends observed in other countries and regions6121319202122232425.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We observed that the crude annual incidence of PLA and KP-PLA increased significantly from 1994–2004 to 2004–2015, which could be due to larger number of inpatients and improved early diagnostic techniques. In short, PLA and KP-PLA are common health problems in mainland China, which consistent with the recent epidemiological trends observed in other countries and regions6121319202122232425.…”
Section: Discussionsupporting
confidence: 87%
“…Klebsiella pneumoniae (K. pneumoniae ) is a gram-negative bacterium. In the late 1980’s, K. pneumoniae induced PLA (KP-PLA) was first described in Taiwan5, and highlighted with subsequent case reports and clinical studies in the Asia-Pacific region678910. Up to now, K. pneumoniae is considered to surpass Escherichia coli (E. coli ) to become the predominant cause of PLA over the past three decades1112.…”
mentioning
confidence: 99%
“…In addition, because of the acquisition of extended-spectrum β-lactamases and carbapenemases, such as the recently described NDM-1 [4], multi, extremely or pan-drug resistant clinical strains are more frequently isolated [5,6]. In addition, K. pneumoniae has re-emerged as a cause of community-acquired infections including pneumonia and the characteristic syndrome of pyogenic liver abscess, with possible complications including endophthalmitis or meningitis [7,8]. K. pneumoniae is, thus, an important virulent pathogen able to cause serious infections in ambulatory, otherwise healthy hosts and to spread within patients [5,9] that requires a better understanding of the molecular mechanisms underlying the various forms of its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Olgumuzda da diabetes mellitus saptanmadı. Yapılan çalışmalarda metastatik infeksiyon sıklığı %9.9-13 arasında değişmekte olup en sık göz tutulumu izlenmektedir (5)(6)(7)15,16). Benzer şekilde olgumuzda da endoftalmi gelişti.…”
Section: İrdelemeunclassified
“…Chang ve arkadaşları (20) tarafından yapılan bir çalışmada K. pneumoniae'ye bağlı tek apsenin varlığıyla metastatik infeksiyon gelişmesi arasında ilişki olduğu bulunmuştur. Bir diğer çalışmada özellikle diabetes mellitus varlığı ve trombositopeninin saptanması metastatik infeksiyonla ilişkili bulunmuştur (16). Olgumuzun da tek apsesi vardı; ancak diabetes mellitus ve trombositopenisi yoktu.…”
Section: İrdelemeunclassified